Anesthetic Effect of MS-222 on Juvenile Black Rockfish (Sebastes schlegelii) - Lin YANG; Bangyin ZHANG; Zhen MENG; Xiaoxuan SUN; Chuer SONG; Zheng ZHANG; Rongjing XU; Peng SUN (Progress in Fishery Sciences, 2024)
The black rockfish, Sebastes schlegelii, is the main marine fish species produced via offshore cage culture in China. Moreover, it is essential to select a convenient, safe, and harmless anesthetic that can effectively reduce the physiological stress response of juveniles during land–sea relay transport. MS-222 has been widely used in fish and other aquatic creatures during handling and transportation because of its secure induction and rapid recovery. In this study, the anesthetic effect of MS-222 (tricaine methanesulfonate; anesthetic effect: 20–130 mg/L, interval of 10 mg/L, total of 12 concentration gradients; simulated transportation: 30–60 mg/L, interval of 10 mg/L) on three specifications of juvenile black rockfish (W10, W40, and W80; average body weight of (10.11±2.13) g, (42.38±5.19) g, and (80.79±6.65) g, respectively) was investigated. The times to deep sedation (A2) and anesthesia (A4) under different concentrations of MS-222 and the optimal sedation and anesthetic concentrations of MS-222 were determined. The results showed that in water with a temperature of (14.5±0.5) ℃, pH of 7.85, salinity of 30 and dissolved oxygen concentration above 7.5 mg/L, the time required for W10, W40, and W80 juveniles to reach the A2 and A4 stages decreased with an increase in anesthetic concentration and increased with an increase in body weight at the same anesthetic concentration. Quadratic regression analysis was performed to analyze the relationship between the A2 and A4 stage effect times and the concentrations of MS-222. The equations describing the relationship between the A2 stage effect time (y) and anesthetic concentration (x) in W10, W40, and W80 groups were y = 0.210 7x2 - 21.207x + 602.6 (R2 = 0.95), y = 0.202 1x2 - 21.501x + 642.6 (R2 = 0.98) and y = 0.089 3x2 - 14.153x + 606 (R2 = 0.91), respectively. Those for A4 stage effect time and the concentration of MS-222 were y = 0.043 1x2 - 10.755x + 813.57 (R2 = 0.97), y = 0.062 1x2 - 16.221x + 1 205.6 (R2 = 0.97) and y = 0.059 6x2 - 15.954x + 1 229.9 (R2 = 0.92), respectively. Therefore, the optimal sedative and anesthetic concentrations of MS-222 for juvenile W10, W40, and W80 black rockfish were 27.38, 29.94, and 40.39 mg/L (A2), and 95.32, 107.32, and 116.58 mg/L (A4), respectively, according to the optimal effect time of 180 s. No significant difference was observed between the respiratory rates of juvenile fish in the A2 stage and those in the control group; however, the respiratory rates of juvenile fish in the A4 stage gradually decreased with an increase in anesthetic concentration and were significantly lower than those of the control group (P < 0.05). The results of simulated transport over 8 h demonstrated that the survival rate of all fish remained at 100% within a concentration range of 30–50 mg/L for MS-222. However, when the concentration reached 60 mg/L, the survival rate decreased to approximately 60% for the W10 group and 80% for the W40 group, though it was still maintained at 100% for the W80 group. Therefore, suggested transport concentrations for juvenile W10, W40, and W80 black rockfish are in the ranges of approximately 27.38–50.00, 29.94–50.00, and 40.39–60.00 mg/L, respectively. These findings provide valuable guidance for the safe transportation of juvenile black rockfish during stock enhancement and offshore cage land-sea transportation. Moreover, the optimal anesthetic concentration can serve as a reference point for biological experiments involving measurement, labeling, or sample collection with juveniles of varying sizes.